States constrain-based algorithm for large scale regular expression matching - Wei HE; Yun-fei GUO; Hong-chao HU (Tongxin xuebao)
By analysis of state explosion in deterministic finite automata DFA,a novel algorithm Group2-DFA based on state constrains was proposed to reduce the memory usage.With the state constrains,states in NFA were classified into several groups.Group2-DFA introduces two-level classification and merges NFA and DFA together to a hybrid FA construction.The experiments show that Group2-DFA can reduce memory usage efficiently and keep high throughput with a small increase of memory reading time.With 300 regex rules,Group2-DFA can cut 75% states and achieve 1Gbps throughput.